ESRA19-0498 Ultrasound guided regional anaesthesia training program in a university hospital in malaysia. (30th August 2019) - Beh, ZY; Lim, SM; Lim, WL; Syahmi, MA; Hasan, MS
Abstract : Background and aims: Regional anaesthesia is a vital skill for anaesthesiologists and ultrasound-guided techniques have enhanced the skill. Prior to this, ultrasound guided regional anaesthesia (UGRA) training in our institution was conducted on a case-by-case basis without a dedicated team, block room and limited supervision. We launched a training programme in mid-2018 as part of the quality improvement initiative. Methods: This training module is implemented using the Plan-Do-Study-Act (PDSA) framework. Baseline: A block area, information leaflet and database registry were created. Residents were assigned to undergo one month regional anaesthesia and acute pain medicine (RAPM) posting. They got to perform blocks under supervision, learned fundamentals and follow up patients who received blocks. Residents had to attend UGRA workshop before starting their posting. PDSA 1: A one–day workshop consist of essential lectures, hands–on scanning on volunteers and needling practice on cadavers. PDSA 2: Further programme refinement – two–days workshop, more hands–on stations, collaboration with external facilitators. PDSA 3: Developed formal assessment tools for participants during workshop and RAPM posting, end–of–posting exam. PDSA 4: Purchased simulator and anatomy app, self manufactured 3D training simulator to enhance teaching and practice. Results: We had conducted 5 workshops involving 82 residents, 22 fresh cadavers and 16 qualified regional anaesthesiologists to facilitate the program. 58 of the residents had completed their RAPM postings. None of them failed the assessment. The participants' confidence level in performing basic peripheral nerve blocks was significantly increased. Conclusions: Our training programme underpin a novel effort to provide a comprehensive UGRA training for anaesthesia residents in Malaysia.